KULINER SEBAGAI WARISAN BUDAYA: STUDI KASUS PELESTARIAN MAKANAN TRADISIONAL WINGKO BABAT DI ERA GENERASI MILENIAL - Madani Waskita Putra Nagari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study examines the preservation of Wingko Babat, a traditional Indonesian culinary product, as a form of local cultural heritage amid social changes and shifting consumption patterns among the millennial generation. Wingko Babat functions not only as a food product but also as a representation of cultural identity, collective memory, and local values within the Babat community of Lamongan Regency. This research employs a qualitative approach with a case study design to explore cultural meanings, millennial perceptions, and preservation strategies implemented by local producers, community groups, and local government. Data were collected through field observations, in-depth interviews with Wingko Babat producers, millennial consumers, and sub-district officials, as well as documentation of production and promotional activities. The findings indicate that the millennial generation plays a strategic role in preserving Wingko Babat through packaging innovation, product diversification, the use of social media, and digital marketing strategies based on cultural storytelling. However, preservation efforts continue to face challenges, including weak producer regeneration, limited digital literacy, and competition from modern culinary products. This study highlights the importance of adaptive and collaborative approaches in sustaining traditional culinary heritage as part of Indonesia’s intangible cultural heritage in the digital era. ABSTRAK Penelitian ini mengkaji upaya pelestarian makanan tradisional Wingko Babat sebagai warisan budaya lokal di tengah dinamika sosial dan perubahan pola konsumsi generasi milenial. Wingko Babat tidak hanya berfungsi sebagai produk pangan, tetapi juga merepresentasikan identitas budaya, memori kolektif, dan nilai-nilai lokal masyarakat Babat, Kabupaten Lamongan. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus untuk menggali makna kultural, persepsi generasi milenial, serta strategi pelestarian yang dilakukan oleh pelaku usaha, komunitas lokal, dan pemerintah setempat. Data dikumpulkan melalui observasi lapangan, wawancara mendalam dengan produsen Wingko Babat, generasi milenial, dan aparatur kecamatan, serta dokumentasi aktivitas produksi dan promosi. Hasil penelitian menunjukkan bahwa generasi milenial memiliki peran strategis dalam pelestarian Wingko Babat melalui inovasi kemasan, pengembangan varian rasa, pemanfaatan media sosial, dan strategi pemasaran digital berbasis storytelling budaya. Meskipun demikian, pelestarian masih menghadapi tantangan berupa lemahnya regenerasi produsen, keterbatasan literasi digital, dan persaingan dengan produk kuliner modern. Penelitian ini menegaskan pentingnya pendekatan adaptif dan kolaboratif dalam menjaga keberlanjutan kuliner tradisional sebagai bagian dari warisan budaya takbenda di era digital.